The Influence Of Financial Ratios And Industry Specifics On The Profitability Of Sharia Banking Companies With Credit Risk As Moderator - Wardani, Alfionita Kusuma; Abdani, Fadlil (Fakultas Ekonomi Universitas Negeri Manado, 2024)
The main objective of this research is to examine the influence of financial ratios on the profitability of companies, with credit risk as a moderating variable. The population in this study includes all banking companies registered with the Financial Services Authority (OJK) from 2019 to 2023. The analysis used includes panel data selection tests. This study found that current ratio can affect a company's profitability because the company has enough current assets to cover its short-term liabilities, while the debt to equity ratio and industry specifics do not affect the company's profitability. Additionally, this research can provide information related to the factors that influence the profitability of Islamic banking companies, so that companies can improve their profitability. Furthermore, for investors, this research can also serve as a consideration for assessing the profitability of Islamic banking companies before investing.